2019
DOI: 10.3389/fphys.2019.00896
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing at the Nuclear Envelope by Nuclear Pore Complex Stretch Activation and Its Effect in Physiology and Pathology

Abstract: Cell fate is correlated to mechanotransduction, in which forces transmitted by the cytoskeleton filaments alter the nuclear shape, affecting transcription factor import/export, cells transcription activity and chromatin distribution. There is in fact evidence that stem cells cultured in 3D environments mimicking the native niche are able to maintain their stemness or modulate their cellular function. However, the molecular and biophysical mechanisms underlying cellular mechanosensing are still largely unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 124 publications
(221 reference statements)
1
46
0
1
Order By: Relevance
“…Mechanotransduction even involves the nuclear envelope and nuclear pore structures as an upcoming new field of mechanobiological coupling, where deformations are followed by changes in the passage of molecules in and out of the nucleus and also changes in chromatin packing and architecture [30,31]. A recent review describes the microenvironmental changes in both osteocytes and muscle stem cells in response to mechanical cues, with a special focus on the respective cellular microenvironment.…”
Section: Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…Mechanotransduction even involves the nuclear envelope and nuclear pore structures as an upcoming new field of mechanobiological coupling, where deformations are followed by changes in the passage of molecules in and out of the nucleus and also changes in chromatin packing and architecture [30,31]. A recent review describes the microenvironmental changes in both osteocytes and muscle stem cells in response to mechanical cues, with a special focus on the respective cellular microenvironment.…”
Section: Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…It was later shown that by twisting fibronectin-coated magnetic beads attached to the cell surface, one could induce stretching of chromatin and subsequent upregulation of transcription activity (Tajik et al 2016). The distribution of stresses along the nuclear lamina is believed to be the primary mechanism responsible for such responses (Enyedi and Niethammer 2017), which has led to the hypothesis of stretchactivation along the nuclear envelope (Donnaloja et al 2019). By connecting expression levels of lamin A/C to resistances to change in nuclear surface area and consequently the nuclear stretch modulus, we have shown the relevance of lamin A/C to mechanoresponses governed by stretches in the nuclear envelope.…”
Section: Nuclear Morphology and Functionmentioning
confidence: 99%
“…Increases in the volume of nuclei either through swelling (Finan, Leddy, and Guilak 2011) or directed migration on patterned substrates has been shown to decondense or dilate chromatin levels. Stretching of the nuclear surface area is thought to be a mechanism of nuclear mechanotransduction (Enyedi and Niethammer 2017;Donnaloja et al 2019). Nuclear morphology is also characterized in part by local curvature; regions of high local curvature have been linked to nuclear rupture (Xia et al 2018) and nuclear blebs (Stephens et al 2018;Cho et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is essential to understand the molecular mechanisms in genome regulation mediated by NPC and Nups and how these genome regulations subsequently influence the cell fate. Recently a comprehensive review (Donnaloja et al, 2019) regarding the prospective role of Nups in the mechano-transduction has been published. They proposed a model, wherein application of mechanics from the Sun1 protein of Linker of Nucleoskeleton and Cytoskeleton to Nup153 causes the nuclear stretch which ultimately affects the nuclear transport in mechanics.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%